A new jellynose, Ateleopus edentatus, from the western Pacific Ocean (Teleostei: Ateleopodiformes: Ateleopodidae) - Kaga, Tatsuya (Zootaxa, 2016)
Ateleopus edentatus sp. nov. is described based on 12 specimens collected from the Kyushu-Palau Ridge in the western Pacific Ocean. It is distinguished from its three known congeners in completely lacking upper-jaw teeth. It is also distinguished from Ateleopus indicus by having 94–130 anal+caudal-fin rays vs. 76–82 in A. indicus, 11–13 gill rakers vs. 7–8, and 26–28+81–107=109–135 vertebrae vs. 22–24+75–80=97–103.